¿Es la cereza electrónica una solución para mitigar el Pitting? - Clemares, Nicolas; Manavella, Fernando Ariel; Moltoni, Andres Fernando; Arhancet, Juan Santiago; San Martino, Liliana (AAPRESID, 2024)
Poster